China Belt and Road Initiative:: Ties that Bind or Choke Development in the East and Southern Africa Subregions - DZEKASHU, WILLIAM (Archives of Business Research, 2021)
Most of Sub-Sahara Africa gained independence from Europe in a wave from 1957 through the late 1980s with the notion that her former colonial masters would be development partners in the newfound era of political, social, and economic freedom. This perception of partnership is evidenced in the Gross Domestic Product (GDP) growth, but regrettably, in other countries in the continent, there have been delays in infrastructure development. With Europe’s failure to meet the expectation, Africa has turned to China as a development partner. China has tackled some of the urgent infrastructure needs in return for agricultural products and natural resources. This recent partnership with China continues to expand in Africa, demonstrated by the launching of the Belt and Roads Initiative (BRI). East and Southern Africa represent the highest beneficiaries of the BRI engagements, receiving over half of the Foreign Direct Investment (FDI) from China whose foreign investment practices in Africa have come under great criticism from the West. This skepticism is due to the vague nature of the engagements and notes which are not publicly reported. This persistent suspicion by the West calls for close monitoring of the relations between the US and China that could easily escalate to a conflict between both nations. Though under attack, BRI has scored great instances of success through the execution of major infrastructure and commercial projects in partner nations. An issue of focus addressed here is whether the engagements with China represent sustainable relationships for development.